The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/2193-1801-3-516
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SHF and SSF of wet exploded corn stover and loblolly pine using in-house enzymes produced from T. reesei RUT C30 and A. saccharolyticus

Abstract: The aim of the present study was to compare bioethanol production from wet exploded corn stover (WECS) and loblolly pine (WELP) hydrolyzed with in-house and commercial enzymes and fermented separately (SHF) and simultaneously (SSF). In-house enzymes produced from Trichoderma reesei, RUT-C30 and a novel fungal strain, Aspergillus saccharolyticus were loaded as 5 and 15 FPU/g glucan and supplemented with 10 and 30 CBU/g glucan, respectively. For hydrolysis and fermentation, slurries of WECS and WELP at 5 and 10%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…The EY % displayed in Table 6 are in accordance with a recent study (Rana et al, 2014) which carried out a comparison between SHF and SSF processes, varying the solid loadings (5-10%) and enzyme dosages (5-15 FPU/g glucan) employing two different raw materials (corn stover and loblolly pine). In all the trials, the SSF process showed higher final ethanol concentrations for both types of feedstock.…”
Section: Samplesupporting
confidence: 84%
“…The EY % displayed in Table 6 are in accordance with a recent study (Rana et al, 2014) which carried out a comparison between SHF and SSF processes, varying the solid loadings (5-10%) and enzyme dosages (5-15 FPU/g glucan) employing two different raw materials (corn stover and loblolly pine). In all the trials, the SSF process showed higher final ethanol concentrations for both types of feedstock.…”
Section: Samplesupporting
confidence: 84%
“…Novozyme 188 showed higher hemicellulose-specific (mannanase and xylanase) activities, which also contributed towards its saccharification ability. Our data show that Novozyme 188 is indeed a suitable supplementary enzyme for reinforcing T. reesei cellulase, which remains the traditionally favorable enzyme mixture for lignocellulosic materials degradation (19,31).…”
Section: Discussionmentioning
confidence: 95%
“…The difference between the optimum conditions for enzymatic hydrolysis and those for fermentation could cause problems (39). However, a comparison of SHF and SSF conducted by Rana et al (40) found that SSF was more efficient than SHF, despite using a lower reaction temperature, which is suboptimal for enzyme hydrolysis. The lower temperatures and shorter operating times required for SSF processes result in energy savings, which are a significant advantage of the system (16,41).…”
Section: Separate Hydrolysis and Fermentation (Shf)mentioning
confidence: 99%